PERAN MASJID DI LINGKUNGAN MASYARAKAT HETEROGEN PADA MASA PANDEMI COVID 19 - Een Suryani; Nunung Nurhayati; Khaerul Wahidin; Muhammad Azka Maulana (An-Nufus, 2020)
This study aims to analyze the role of mosques in a heterogeneous society during the Covid 19 pandemic. The research method of this research is through literature review plus cultivating data by interviews and direct observation.. Mosques have a very strategic role in building tolerance and a spirit of religious moderation in a heterogeneous society. This research found that mosques were not just places of worship for spiritual strengthening but also played a role in preventing the spread of the Covid 19 virus.